2009
DOI: 10.1075/japc.19.1.03sze
|View full text |Cite
|
Sign up to set email alerts
|

Functions and genres of ESL children’s English writing at home and at school

Abstract: Drawing on a sociocultural perspective of genre as a social action situated in a particular context, this study examined the functions and genres of four second-grade ESL (English as a Second Language) children’s English writing at home and at school. The two boys and two girls were born and raised in Canada, speaking English at school and with their siblings, and Cantonese at home with their parents. A total of 67 pieces of school writing and 54 pieces of home writing were collected over a five-week period. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Even when the same activities could be found both in school and at home, they tended to have different orientations (Orellana & Reynolds 2008), or to be characterized by different functions and genres (Sze, Chapman & Shi 2009). Orellana & Reynolds’ years of observation and interviews showed that Spanish-speaking 10- to 12-year-olds had different experience with paraphrasing at home and school.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when the same activities could be found both in school and at home, they tended to have different orientations (Orellana & Reynolds 2008), or to be characterized by different functions and genres (Sze, Chapman & Shi 2009). Orellana & Reynolds’ years of observation and interviews showed that Spanish-speaking 10- to 12-year-olds had different experience with paraphrasing at home and school.…”
Section: Resultsmentioning
confidence: 99%
“…Characterized by clear purpose, a visible and interactive audience, and much participant freedom, contextualized paraphrasing at home enabled the child to simultaneously deal with two languages at the same time, in great contrast to the rather bland and decontextualized school paraphrasing. Similarly, in Canada, with Cantonese-speaking second-graders, Sze et al (2009) found that writing at school, mainly consisting of writing a story or a journal, or making a list, was strictly driven by the need to acquire and practice literacy skills. However, at home, these same children were exposed to a much richer variety of literary genres, such as poems, cards, notes, and non-fiction texts, and even actively engaged in writing these types of texts for the purpose of interacting.…”
Section: Resultsmentioning
confidence: 99%